Laboratory and surveillance studies following a suspected Dengue case in Greece, 2012. (January 2015) - Papa, Anna; Gavana, Elpida; Detsis, Marios; Terzaki, Eirini; Veneti, Lambrini; Pervanidou, Danai; Georgakopoulou, Theano; Marangos, Markos; Koliopoulos, George; Baka, Agoritsa; Tsiodras, Sotirios; Tsakris, Athanasios; et al.
Highlights: Detailed laboratory investigation excluded Dengue virus infection in a case with fatal outcome. There is a need for industries to improve the immunometric assays to avoid interference with rheumatoid or other factors. Increased awareness is needed for the evaluation of the diagnostic assays for flavivirus infections. Surveillance study in the region showed no evidence of Dengue virus circulation, high seroprevalence to West Nile virus (6.1%) and detection of two acute phlebovirus infections. Entomological investigations showed the presence of Aedes albopictus mosquitoes. Abstract: Objectives: To describe the laboratory assays used to investigate a suspected dengue case in summer 2012 in western Greece and to report the public health response. Design of methods: Samples from the patient were tested for detection of Dengue virus (DENV) antibodies, NS1 antigen and RNA. Public health professionals interviewed residents of the village, and blood samples taken from 132 persons were tested for antibodies for DENV and West Nile virus (WNV). Samples from 10 persons who reported symptoms in the prior 15 days (including 3 persons who had fever at the time of sampling) were tested for DENV, WNV and additional arboviruses. Entomological missions were organized in the area of potential exposure to investigate the presence of competent DENV vectors. Results: Based on a combination of serological and molecular methods, DENV infection was excluded, and the problems in the serology, especially in the DENV NS1 antigen, were attributed to interfering factors. A 6.1% WNV seroprevalence was detected in the region, and phlebovirus IgM and IgG antibodies were detected in two of three persons who had fever at the time of sampling. Aedes albopictus adult mosquitoes were present in the region. Conclusions: A multi-disciplinary field and laboratory investigation showed no evidence of DENV infection. There is a need for industries to improve the immunometric assays to avoid interference with rheumatoid or other factors, and increased awareness is needed for the evaluation of the diagnostic assays. The high WNV seroprevalence in the investigated region highlights the need for strengthening awareness on vector borne diseases. The presence of Ae. albopictus suggests that the possibility of introduction of DENV exists, and preparedness plans are needed.